228k views
3 votes
Factor the polynomial completely given that k=4 is a zero. Also list the zeroes of P(x).

P(x) x^4-2x^3-7x^2-4x

1 Answer

5 votes

If it is known that k=4 is polynomial's zero, then the polynomial should have x-4 as its factor.

Factor the polynomial:

1)
P(x)=x^4-2x^3-7x^2-4x=x(x^3-2x^2-7x-4)

2) Consider the polynomial
x^3-2x^2-7x-4=x^3-4x^2+4x^2-2x^2-7x-4=x^2(x-4)+2x^2-7x-4=x^2(x-4)+2x^2-8x+8x-7x-4=x^2(x-4)+2x(x-4)+(x-4)=(x-4)(x^2+2x+1)

3) The expression
x^2+2x+1 is a perfect square:


x^2+2x+1=(x+1)^2

Therefore,


P(x)=x(x-4)(x+1)^2.

Answer:
P(x)=x(x-4)(x+1)^2. Zeroes: 0, 4, -1 (twice)

User Phunder
by
5.8k points